Mixed-Reality and Traditional Flight Simulators for Urban Air Mobility Vehicles - Bergman, Keegan (Proceedings of the Wisconsin Space Conference, 2019)
The 2018 NASA Academy at Langley Research Center created proof-of-concept mixed reality (MR) and traditional simulators to enable quick vehicle concept prototyping and data collection for human factors studies. Urban Air Mobility (UAM) vehicle concepts were implemented as the focus for these simulators due to recent and dramatic rise in subject interest. The team used X-Plane 11 to model flight dynamics, and Unity for the virtual reality (VR) aspect of the MR simulator and to model the control panel in the traditional simulator. A physical version of the virtual control panel was also fabricated to provide haptic feedback to maintain the immersion for the MR simulator.